Determination of Metal Cadmium (Cd), Copper (Cu), Iron (Fe) and Zinc (Zn) in Drinking Water from The Boring Well of Surbakti Village, Karo District by Atomic Absorption Spectrophotometry Method - Zul Alfian; Ria Ardianti Lubis; Harry Agusnar (Journal of Chemical Natural Resources, 2024)
Water is an essential requirement for human existence. In addition to traditional water usage, water is essential for enhancing the quality of human existence and facilitating industrial and technological endeavors. An investigation was conducted on the contents of Cadmium (Cd), Copper (Cu), Iron (Fe), and Zinc (Zn) in drinking water from drilled wells in Surbakti Village, Karo District, employing Atomic Absorption Spectrophotometry (AAS) techniques. Sampling occurred during weeks 1, 2, 3, 4, and 5 and was subsequently digested with concentrated nitric acid until a volume of 15 mL was attained. The metal concentrations of Cd, Cu, Fe, and Zn were quantified using Atomic Absorption Spectroscopy (AAS) using a calibration curve. The findings indicated a concentration of Cd at 0.0031 mg/L, Cu at 0.0470 mg/L, Fe at 0.2741 mg/L, and Zn at 0.2929 mg/L. In this instance, Cd produced a greater concentration of drinking water standards compared to Cu, Fe, and Zn. Nonetheless, it nonetheless met the drinking quality standards established by Regulation Minister of Health No. 492/Menkes/Per/VII/2010.